Implantação de um sistema da qualidade em uma microcervejaria com foco no controle microbiológico - Barreto, Hannah Barbara Batista (Universidade Federal Rural do Semi-Árido, 2019)
Microbiological control in a brewery is of paramount importance since each yeast or micro-organism guarantees particular sensory and physicochemical properties to the beverage. In a brewing process, specific and suitable yeast is usually added to a sterile must, as the main problem encountered is that the contaminants can produce off-flavors, that is, they add bad flavors to the beer, and in addition they may contain microorganisms pathogenic to human health. The objective of this study is to evaluate if sanitary measures are being applied correctly, verifying if there is contamination in the final product and, in addition, to investigate and map possible foci of contamination in the process, suggesting preventive and corrective actions to control failures and to follow good manufacturing practices in the brewing industry. The PDCA cycle guided decision-making, including the implementation of the 5S methodology in the plant, the elaboration of an action plan and the use of control sheets to improve information management. Through samples taken during the production process it was verified that the beers were not meeting the microbiological standard determined by ANVISA, legal responsible. For this, parameters were established for preventive and corrective actions.
Monografia
Keywords: Contaminação; Cervejaria; Pasteurização; Contamination; brewery; pasteurization; ENGENHEARIAS::ENGENHARIA QUIMICA